IMPACT OF IN-BOUND LOGISTICS COSTS ON INDUSTRIAL PERFORMANCE IN NIGERIA - Gabriel Oni, Babatope; Joel Ojekunle, Ademola (African Journal of Social and Behavioural Sciences, 2024)
The Nigerian industrial sector, particularly in manufacturing, has been characterized by low performance. This paper explores the influence of in-bound logistics costs from Nigerian firms’ importation on industrial performance, using seaport import clearance cost and manufacturing businesses’ turnover, sales cost, and profit as proxy metrics. A survey was conducted on 23 Nigerian Stock Exchange-listed firms that regularly import goods via seaports through a questionnaire. The study collected primary data and time-series data from secondary sources over a ten-year period. This paper utilized the vector error correction model to reveal that the total import clearance cost significantly and positively impacts the industrial performance of the sampled firms in the long run. This paper revealed that throughout a ten-year period (2010-2019), a 10% increase in the total cost of import clearance resulted in increases of 2.4%, 1.99%, and 1.98% in turnover, sales cost, and profit, respectively. Additionally, the adjusted R-square shows that the total import clearance cost explains approximately 86.3%, 84.4% and 83.8% of the total variation in turnover, sales cost and profit respectively. The study indicates that industrial performance in Nigeria heavily relies on in-bound logistics from firms’ material import, highlighting the significant impact of the trade logistics environment on industrial development.